KENDALA DALAM IMPLEMENTASI E-GOVERNMENT PADA PEMERINTAH KABUPATEN PIDIE - Rahmat Musfikar (UIN Ar-Raniry, 2018)
Nowadays, we are faced with technological era, where the use of information and communication technology in the world is growing rapidly. The government program to realize the application of technology information is E-Government. The implementation of E-Government in Indonesia is highly growing and there are laws and regulations on E-Government from Indonesia government. Currently, the Government of Indonesia has reached the stage of evaluation through E-Government Rating Indonesia. This study aimed to know the obstacles in implementing E-government in Pidie district government. This study used previous studies, frameworks and theories to create a suitable new model in Pidie District. To propose a new model, this study attempted to combine, synthesize and conduct a re-factor. The methodology used in this study is a quantitative approach by using questionnaire distribution technique to government employees. The method for sampling used is nonprobability technique namely purposive sampling. Data analysis technique used in this research is Partial Least Square (PLS). The technique used to test the hypothesis statistically is bootstrapping on the PLS. The hypothesis proposed in the study is that there were 3 obstacles in implementing e-government in Pidie district government. The results of this study shows that the obstacles that greatly affected the implementation of e-government in Pidie government was the organizational factor, while the other two factors, Human Resources (HR) and the infrastructure factor, did not show a significant effect.